1987
DOI: 10.1073/pnas.84.21.7681
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of a clonal bone marrow stromal cell line in vivo stimulates hematopoietic recovery from total body irradiation.

Abstract: Whether bone marrow stromal cells of donors contribute physiologically to hematopoietic stem cell reconstitution after marrow transplantation is unknown. To determine the transplantability of nonhematopoietic marrow stromal cells, stable clonal stromal cell line (GB1/6) expressing the a isoenzyme of glucose-6-phosphate isomerase (Glu6PI-a, D-glucose-6-phosphate ketol-isomerase; EC 5.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 22 publications
1
90
0
Order By: Relevance
“…28 Engraftment of a clonal murine bone marrow stromal cell line in irradiated mice has been described, which stimulated hematopoietic recovery after total body irradiation. 29 Donor stromal cells were detected only in the bone marrow of recipients but other studies indicate an ability for bone marrow stromal cells to engraft other tissues as well. Expanded cultured adherent cells from the bone marrow of transgenic mice expressing a minigene for human collagen I were injected into irradiated mice and later detected in several tissues: marrow, spleen, bone, lung and cartilage.…”
Section: Figurementioning
confidence: 96%
“…28 Engraftment of a clonal murine bone marrow stromal cell line in irradiated mice has been described, which stimulated hematopoietic recovery after total body irradiation. 29 Donor stromal cells were detected only in the bone marrow of recipients but other studies indicate an ability for bone marrow stromal cells to engraft other tissues as well. Expanded cultured adherent cells from the bone marrow of transgenic mice expressing a minigene for human collagen I were injected into irradiated mice and later detected in several tissues: marrow, spleen, bone, lung and cartilage.…”
Section: Figurementioning
confidence: 96%
“…7,29,30 A number of preclinical animal models of stromal cell transplantation have been established to support hematopoietic engraftment, including using human fetal lung-derived MSCs. [31][32][33] Both autologous and allogeneic human marrow stromal cells were shown to improve the quantity and duration of human hematopoietic engraftment in a preimmune sheep model. 34 Angelopoulou et al 35 recently reported that cotransplantation of human MSCs enhanced myelopoiesis and megakaryopoiesis in NOD-SCID mice transplanted with the limiting doses of peripheral blood CD34 þ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, and the studies of others, indicate that stromal cell infusion can influence host hematopoiesis 14,15,33,34 and suggest that this approach has possible application in cell and/or gene therapy. 35,36 The use of stromal cells has the added dimension of extensive transdifferentiation potential to osteoblasts, chondroblasts, 37,38 fibroblasts, 39 muscle, 40 astrocytes, 41 and neurons.…”
Section: Discussionmentioning
confidence: 86%
“…14 Anklesaria et al 15 showed that infusion of a transformed stromal cell line into irradiated and splenectomized Sl/Sl d mice could partially correct their anemia. The aim of our study is to extend this observation by transplanting normal stromal cells, derived from long-term bone marrow cultures, into unconditioned Sl/Sl d recipients as a model for human cell therapy.…”
mentioning
confidence: 99%